Assessment of pyrethroid contamination and potential mitigation strategies in California Central Coast surface waters. (15th January 2021) - DeMars, Christopher; Wang, Ruoyu; Grieneisen, Michael L.; Steggall, John; Zhang, Minghua
Abstract: Increased use of pyrethroids in the Central Coast of California since 2011 has resulted in a dramatic increase in the number and proportion of surface water samples with detectable concentrations at levels of concern to the public and state regulators. The goals of this study were to investigate the relationships between pyrethroid usage and environmental contamination, quantify and assess the potential risks, and recommend mitigation strategies. This study compiled the available pyrethroid use and surface water sampling data for the region, and then applied GIS methods to dynamic simulation modeling and usage-restriction buffer analyses. The results showed that in Monterey County alone, the agricultural usages of bifenthrin and permethrin each increased by ~50%, and the positive detection frequencies of both also increased around 2011–2013. County-wide, bifenthrin positive detections in surface water samples increased precipitously from 8.2% (7/85) for 2008–2012 up to 36.4% (106/291) for 2013–2017, and detections above its crustacean LC50 concentration went from 7.1% (6/85) to 35.7% (104/291). Despite its higher usage by mass, comparable figures for permethrin were more modest for the same time-periods, with positive detections going from 10.6% (9/85) to 14.4% (64/444), and detections above its crustacean LC50 going from 3.5% (3/85) to 7.2% (32/444). The seasonal lag between high bifenthrin usage in spring/summer and high detections in fall/winter samples showed the best correlations with 128- to 182-day lag times. This timing suggests that fallow season rain is likely the main driver of pyrethroid off-site movement into surface waters. SWAT modeling indicated that significant reductions in surface water permethrin concentrations only occurred with buffer distances of 1.6–3.2 km, but not with narrower buffers. However, if those wider buffers were implemented, permethrin could no longer be used on the majority of land where it is currently applied. Specifically, a 1.6-km buffer reduced the instream concentration by 8% but impacted 50% of the cropland, and a 3.2-km buffer reduced the concentration by 50% while impacting 76% of cropland. This study suggested that more promising alternative management practices could include an overall reduction in pyrethroid usage back to 2011 levels or other active mitigation strategies, like planting cover crops during the fallow winter wet season, or installing either vegetated buffer strips and/or sediment check dams on small tributaries to minimize sediment runoff. Highlights: California Central Coast pyrethroid use & surface water detections rose after 2011. Most pesticide use in spring/summer growing season; detections in fall/winter fallow season. Many detections since 2013 were above toxic levels for fish and invertebrates. SWAT modeling shows reduced loading with less pyrethroid usage near major waterways. Meaningful load reduction required prohibition of pyrethroid use on most agricultural fields.